Saudi Vision 2030: Economic Reforms and Sustainable Development in the Kingdom - Khoirunnisa, Khoirunnisa; Nurhaliza, Syahfira Angela (Journal Public Policy, 2024)
This paper endeavours to scrutinize the ramifications of the economic policy reforms introduced in Saudi Arabia under the rubric of Saudi Vision 2030. Prince Mohammed bin Salman spearheaded this ambitious initiative as a strategic response to the nation's manifold economic challenges stemming from internal and external contingencies. Saudi Vision 2030 is primarily geared towards diminishing Saudi Arabia's reliance on the oil sector, fostering sustainable economic growth, augmenting societal welfare, and enticing foreign investment. Methodologically, the study adopts a Neoliberalism theoretical framework to dissect the implementation of Saudi Vision 2030, emphasizing pivotal concepts such as market liberalization, deregulation, and privatization. Analysis of the socioeconomic impact of the Saudi Vision 2030 program on the Saudi Arabian economy throughout the year 2020 underscores a trajectory marked by positive outcomes. Through a gamut of meticulously crafted programs and initiatives, Vision 2030 has catalyzed substantial transformations, mitigating dependence on the oil sector and broadening the country's economic landscape. Within the inaugural quinquennium, Saudi Arabia has attained commendable milestones, exemplified by heightened public investment, steadfast GDP expansion, diminished unemployment rates, and consolidation of its status as a preeminent global industrial entity.